2022
DOI: 10.1371/journal.pone.0271608
|View full text |Cite
|
Sign up to set email alerts
|

Ogerin mediated inhibition of TGF-β(1) induced myofibroblast differentiation is potentiated by acidic pH

Abstract: Transforming growth factor beta (TGF-β) induced myofibroblast differentiation is central to the pathological scarring observed in Idiopathic Pulmonary Fibrosis (IPF) and other fibrotic diseases. Our lab has recently identified expression of GPR68 (Ovarian Cancer Gene Receptor 1, OGR1), a pH sensing G-protein coupled receptor, as a negative regulator of TGF-β induced profibrotic effects in primary human lung fibroblasts (PHLFs). We therefore hypothesized that small molecule activators of GPR68 would inhibit myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…The increased expression of HIF‐1α supports the premise that fibroblasts within fibroblastic foci and the fibrotic interstitium of IPF tissue are subjected to cellular hypoxia due to impaired diffusion (Higgins et al, 2007). Whether due to metabolic reprogramming and aerobic glycolysis or to impaired oxygen diffusion to fibroblasts in the alveolar interstitium, elevated lactic acid levels have been found in lung tissues from IPF patients (Bell et al, 2022; Kottmann et al, 2012). However, the precise mechanism(s) driving lactate generation in fibrotic lung fibroblasts and the potential role of lactate‐induced cellular signaling on fibroblast phenotype are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased expression of HIF‐1α supports the premise that fibroblasts within fibroblastic foci and the fibrotic interstitium of IPF tissue are subjected to cellular hypoxia due to impaired diffusion (Higgins et al, 2007). Whether due to metabolic reprogramming and aerobic glycolysis or to impaired oxygen diffusion to fibroblasts in the alveolar interstitium, elevated lactic acid levels have been found in lung tissues from IPF patients (Bell et al, 2022; Kottmann et al, 2012). However, the precise mechanism(s) driving lactate generation in fibrotic lung fibroblasts and the potential role of lactate‐induced cellular signaling on fibroblast phenotype are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an acidic microenvironment can liberate latent TGF‐β from the extracellular matrix and contribute to fibrosis by increasing the pool of active TGF‐β (Kottmann et al, 2012). However, a recent study also reported that an acidic pH regulates Ogerin (GPR‐68)‐mediated inhibition of TGF‐β signaling (Bell et al, 2022), demonstrating the complexity of TGF‐β activation and signaling responsiveness. GPR‐68 is a G‐protein‐coupled receptor, and GPRs comprise the largest transmembrane receptor family in humans (Bockaert & Pin, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OGR1 has been implicated in allergen-induced hyper-responsiveness and idiopathic pulmonary fibrosis [ 3 , 10 , 56 , 57 ] and was reported to be pro-inflammatory [ 29 , 56 ]. It is expressed in lung fibroblasts [ 3 , 56 ] and bronchial smooth muscle cells [ 10 , 29 ].…”
Section: Lungmentioning
confidence: 99%
“…OGR1 has been implicated in allergen-induced hyper-responsiveness and idiopathic pulmonary fibrosis [ 3 , 10 , 56 , 57 ] and was reported to be pro-inflammatory [ 29 , 56 ]. It is expressed in lung fibroblasts [ 3 , 56 ] and bronchial smooth muscle cells [ 10 , 29 ]. Whilst OGR1 expression is increased in bronchial smooth muscle cells in an ovalbumin antigen-challenged murine asthma model [ 10 ], it is downregulated in fibroblasts from patients with idiopathic pulmonary fibrosis [ 65 ], which promotes myofibroblast differentiation, suggesting that OGR1 has anti-fibrotic effects in lung fibroblasts [ 56 ].…”
Section: Lungmentioning
confidence: 99%